Peter Canisius and the Development of Catholic Education in Germany, 1549–97 - Atherton, Ruth (Studies in church history, 2019)
The Jesuit Peter Canisius (1521-97) became widely respected as a catechist, pedagogue and preacher who worked tirelessly on behalf of the Catholic faith. Canisius's set of three catechisms - the Large, Small and Smaller - were the most popular and widely available Catholic catechisms in sixteenth-century Germany: by his death, at least 357 editions had appeared, in a number of languages. Employed in Catholic schools, churches and homes across the Holy Roman Empire, his catechisms have been interpreted as a direct response to the Protestant attack on Catholicism in Germany. However, the boundaries between Catholicism and heresy were not always clear to the laity. Drawing on examples from his catechisms and his approach to the Index of Prohibited Books, this article suggests that Canisius sought to promote a policy of inclusion among his fellow Catholics in a time of conflict and uncertainty. In recognizing the distinct nature of German Catholicism, Canisius advocated a tailored educational approach to contentious doctrines and practices. Directed towards the German laity, this approach taught the lesson of compromise and acceptance among those who identified as Catholic. The article adds to existing scholarship on Jesuit education, Canisius's contribution to the development of a German religious identity, Jesuit casuistry and the dissemination of religious knowledge in German society.